2020
DOI: 10.26803/ijlter.19.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Critical: In-service Teachers’ Perspectives on Multicultural Education

Abstract: Many in-service teachers take a passive position regarding multicultural issues such as race, class, ethnicity, socio-economic, religion, gender, and sexual orientation. This passive position impacts classroom dynamics and has social justice consequences. The present qualitative study focuses on 12 in-service teachers' perspectives on multicultural issues. It describes the transformation of their perspectives and practices as they take a semester-long course on diversity. Data sources include the participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Culturally responsive teaching involves actively challenging stereotypes, biases, and misconceptions that may exist within the classroom and society at large. Educators play a critical role in promoting cultural understanding, empathy, and critical consciousness among students, encouraging them to question stereotypes and biases and to critically analyze information from multiple perspectives (Pourdavood et al, 2020). One strategy for challenging stereotypes and biases is to incorporate diverse perspectives and counter-narratives into the curriculum.…”
Section: Foundational Principles Of Inclusive Curriculum Designmentioning
confidence: 99%
“…Culturally responsive teaching involves actively challenging stereotypes, biases, and misconceptions that may exist within the classroom and society at large. Educators play a critical role in promoting cultural understanding, empathy, and critical consciousness among students, encouraging them to question stereotypes and biases and to critically analyze information from multiple perspectives (Pourdavood et al, 2020). One strategy for challenging stereotypes and biases is to incorporate diverse perspectives and counter-narratives into the curriculum.…”
Section: Foundational Principles Of Inclusive Curriculum Designmentioning
confidence: 99%
“…Additionally, teachers may influence peers to interact with immigrant students, opening a culturally diverse experience which is why their perspectives are vital to their experience (Chiofalo et al, 2019b). Pourdavood & Yan (2020) find that "teachers' perceptions and attitudes influence their expectations and treatment of the learners, which may directly impact students and cause them to exhibit either positive or negative attitudes or behaviors" (p.116). Scholars have looked into Italian teachers' attitudes toward immigrant students and found that school leaders encourage teachers to use the presence of newcomers to encourage the rest of the class to "reflect on the themes of diversity" (Chiofalo et al, 2019b, p. 10).…”
Section: Peers Building Relationships Within the Classroom Can Open I...mentioning
confidence: 99%
“…Thanks to the literature that indicates that higher-order thinking (Alismail, 2016;Hjerm et al, 2018;Moreno, 2015) and Banks's (2008Banks's ( , 2019 social action approach have a positive influence on student learning opportunities and promote diversity, equity, and inclusion in the school and the community, one might assume that all educators would adopt instructional strategies that could encourage higher-level critical thinking. However, insights in recent literature suggest many educators do not follow instructional approaches that would encourage higher-level thinking skills in the way that the social action approach would do (Atwater et al, 2017;Balkaran & Roberts, 2019;Banks, 2008Banks, , 2019.…”
Section: Failure To Meet Higher-order Thinking Skills and The Social mentioning
confidence: 99%